2009
DOI: 10.1051/0004-6361/200912869
|View full text |Cite
|
Sign up to set email alerts
|

Infrared radial velocities of vB 10

Abstract: We present radial velocities of the M8V-type, very low-mass star vB 10 obtained at four different epochs between 2001 and 2008. We use high-resolution (R ∼ 20 000) near-infrared (J-band) spectra taken with the nirspec instrument on the Keck II telescope. Our data suggest that vB 10 shows radial velocity variability with an amplitude of ∼1 km s −1 , a result that is consistent with the recent finding of a massive planet companion around the star. More velocity measurements and a better sampling of the orbital p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…The dispersions of our nightly RV measurements are 143 m s −1 and 351 m s −1 for GJ 752 A and GJ 752 B, respectively (see Figure 3). The scatter in our NIRSPEC RV measurements is smaller than the measurements of Zapatero Osorio et al (2009), which reached an amplitude of 1 km s −1 . Our RV dispersion for GJ 752 B is larger than the 10 m s −1 reached by Bean et al (2009) and could be due the smaller spectral resolution of NIRSPEC compared with CRIRES (R = 24,000 for NIRSPEC versus R = 50,000 for CRIRES).…”
Section: Gj 752 Bcontrasting
confidence: 71%
“…The dispersions of our nightly RV measurements are 143 m s −1 and 351 m s −1 for GJ 752 A and GJ 752 B, respectively (see Figure 3). The scatter in our NIRSPEC RV measurements is smaller than the measurements of Zapatero Osorio et al (2009), which reached an amplitude of 1 km s −1 . Our RV dispersion for GJ 752 B is larger than the 10 m s −1 reached by Bean et al (2009) and could be due the smaller spectral resolution of NIRSPEC compared with CRIRES (R = 24,000 for NIRSPEC versus R = 50,000 for CRIRES).…”
Section: Gj 752 Bcontrasting
confidence: 71%
“…More recently, an ammonia gas cell has been employed to achieve ∼5 m s −1 precision (Bean et al 2010b) over 6 month time‐scales with CRIRES operating at K ‐band wavelengths. This survey (Bean et al 2010a) has not found evidence for the massive planet claimed to be orbiting the low‐mass M dwarf VB 10 (Pravdo & Shaklan 2009; Zapatero Osorio et al 2009).…”
Section: Introductionmentioning
confidence: 89%